Écriture féminine de jeunesse et postulation de l’émergence d’un pays dans Lettre à Tita 2 : entre anti-modernisme, exaltation passéiste et quête éthique - Eyenga Onana, Pierre Suzanne (Romanica Silesiana, 2021)
Children’s literature is sometimes considered to be the poor relation of literary genres throughout the world, as it is often confined to the rank of literature for the very young. Yet, on closer inspection, does this literature not play an important role in establishing national identity? In other words, does it contribute to the spread of tolerance and therefore to living together? Backed by Pierre Barbéris’ sociocriticism and structured in three parts, this contribution first illustrates the motivations behind the characters’ behavioural imposture; then examines the internal components that articulate the novel’s literality. Finally, the analysis shows that Jeanne Abou’ou’s Lettre à Tita 2, beyond the stigmatization of a poorly assumed modernism or the exaltation of traditional values, deeply encapsulates the writer’s desire to postulate an emerging world in which Cameroonians would readily identify themselves.